Edukasi Perkembangan Bahasa dan Bicara Anak Speach Delay - Dina Hidayati Hutasuhut; Dinda Yarshal (Medan Resource Center, 2021)
The problem of speech delay in children is a serious problem that must be addressed immediately because it is one of the most common causes of developmental disorders in children. Several studies in several countries state that about 6 to 8% of preschool children have speech delay problems. Speech delay can be seen from the accuracy of word use, which is characterized by unclear pronunciation and in communicating can only use sign language, so that parents and people who those around him are less able to understand the child, even though the child can actually understand what people are talking about. This speech delay will not only affect the social and personal adjustment of the child, but can also affect the academic adjustment of the child. The method used in the implementation of this service activity is through the method of socialization and simulation approaches in the form of lectures and demonstrations. This service activity was carried out aiming to explain the factors that affect speech delay in children and also the treatment given by parents, teachers and the environment in response to this problem. have their own understanding in dealing with children who are late to speak and design a concept model for developing language skills for children who are late. In the end, the team of service implementation activities through this activity hopes that Nurul Hasanah's teachers can improve students' language development, knowledge and skills in presenting learning that is more attractive to students in learning.